FORMULATION OF CONTAINER TERMINAL COMPETITIVE STRATEGY AT MAKASSAR NEW PORT - Fajar Adhi Nugroho Suratno; Mahlia Muis; Fauziah Umar (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
Container Terminal is the entrance and exit of goods through a port. The purpose of this research is to identify the internal and external environmental factors that determine the development strategy and effective business strategy for the development of makassar new port container terminal. This research is a type of exploratory research by identifying and developing Porter's 5-strength strategy. This research is designed to direct managerial strategy decisions in the development of container competitiveness in Makassar New Port PT. Pelabuhan Indonesia IV (Persero) based on scientific analysis and argumentation. Managerial strategy decisions in this study are within the scope of strategy at the corporate level. The results showed that container development through internal environmental analysis is service oriented to cost efficiency and effectiveness, availability of modern facilities and equipment, and implementing international standard service systems. Container development through external environmental analysis includes Exclusive Port Rights to be utilized in container development, support from local governments for the management of Makassar New Port, and the opening of international-scale logistics delivery lines. Furthermore, an effective strategy for the development of container competitiveness by relying on strategic locations to support container activities and services will facilitate companies in increasing container flow because it is supported by various government regulations and regulations, adding equipment. Container Crane Twin Lift to increase productivity, improve the accuracy of container activities, and capital competence and professionalism of human resources owned by the company.